The honey jar : an Armenian's escape to freedom - Schoettler, Joan (Milk & Cookies, an imprint of Bushel & Peck Books, 2023)
In 1920, eight-year-old Bedros fled Armenia with his young sisters, grandmother, and uncle to escape the Turkish soldiers invading their town. But in the confusion, Bedros lost sight of the adults and was left alone to protect his siblings. Hungry, cold, and overwhelmed with responsibility, Bedros failed to remember his promise to his mother. Told in verse, suspenseful and heart-rending, The Honey Jar depicts a journey from desperation to freedom, anchored in Bedros's promise to return to his native land and to find the one he left behind. His story will touch the hearts of families everywhere, especially those who have experienced the longing for a new life.